(3GdJMQjQ hGdJMHjQ dCbhGd CFeI GdJaSjQ aj eYGfi cdGe GdSejY GdHUjQs - (3LeGd GdOjf CHh YHO Gddg eMeO Hf SdjeGf Hf GdMSf GdHdNj GdebOSj GdMfaj, GHf GdfbjH,J (B698 (3g` s
(3ChdgG (B:s
(3ShQI GdTYQGA hGdcdGe YdjgG ef MjK GdGLeGd hGdJaUjd CeG ef MjK GdELeGd aef SJI YTQ ehVYkG s
(3BNQgG (B:s
(3BNQ GdehLhO efg ShQI GdbUU bhdg (B: (3heYfi EJHY EWdH hEdJeS ajeG Ci HeG CfG Ydjg efg GdCehGd Ci GdLfI HGdUObI hUdI GdQMef s
(3jhLO HjGV CKfGA UaMJi (B354 (3h (B355s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B150s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJaSjQ hYdhe GdbQBfs